2023
DOI: 10.3390/ijms24097939
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Fucoidans from Saccharina latissima Regarding Age-Related Macular Degeneration Relevant Pathomechanisms in Retinal Pigment Epithelium

Abstract: Fucoidans from brown algae are described as anti-inflammatory, antioxidative, and antiangiogenic. We tested two Saccharina latissima fucoidans (SL-FRO and SL-NOR) regarding their potential biological effects against age-related macular degeneration (AMD). Primary porcine retinal pigment epithelium (RPE), human RPE cell line ARPE-19, and human uveal melanoma cell line OMM-1 were used. Cell survival was assessed in tetrazolium assay (MTT). Oxidative stress assays were induced with erastin or H2O2. Supernatants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 84 publications
0
1
0
Order By: Relevance
“…In addition, additional aspects of microglia activation would be of interest, such as cytoplasmic makers, further pro-inflammatory gene expression, or additional interleukin or chemokine secretion. For example, it would be of interest whether the effect would be similar if a Toll-like-receptor (TLR3) antagonist were used, as we have previously shown that several fucoidans can reduce inflammatory activation of RPE cells after TLR-3 activation [ 30 , 52 ]. Also, different timelines of activation and concentrations of fucoidan would be of interest.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, additional aspects of microglia activation would be of interest, such as cytoplasmic makers, further pro-inflammatory gene expression, or additional interleukin or chemokine secretion. For example, it would be of interest whether the effect would be similar if a Toll-like-receptor (TLR3) antagonist were used, as we have previously shown that several fucoidans can reduce inflammatory activation of RPE cells after TLR-3 activation [ 30 , 52 ]. Also, different timelines of activation and concentrations of fucoidan would be of interest.…”
Section: Discussionmentioning
confidence: 99%
“…AMD is a progressive disease that can lead to vision loss in people over the age of 50, thus gaining more and more relevance in aging societies. Dörschmann and the Klettner group [5,6] provided new evidence on how a group of plant polysaccharides, fucoidans, are capable of alleviating the effects of AMD. In their elegant back-to-back studies, they analyzed the true potential of fucoidans in retinal medicine.…”
mentioning
confidence: 99%